Cybersecurity Challenges in Health Informatics: A Framework for Securing Patient Data - Dr. R. Kavitha; Abhilash Sam Paulstin K.C; Dr. Dhivya K; Dr. Anbarasu S; Dr. Angeline Prasanna G (The Bioscan, 2025)
Although the speedy digitization of healthcare systems has improved efficiency and accessibility, it has also led to vast cybersecurity vulnerabilities. Patient data is at the center of attacks because it is often highly sensitive. In this paper, we present the major cybersecurity issues related to health informatics, from data breaches, ransomware attacks, insider threats, to regulatory compliance. We suggest an all-inclusive framework for patient data security application of strong encryption, multi-factor authentication, real-time monitoring with procurement of legal and ethical guidelines. Through this research, we hope to give healthcare organizations real-world solutions to handle cyber threats while keeping patient information safe.